Evaluación objetiva de competencias - Álvaro Sánchez Miralles (Miscelánea Comillas, 2016)
Objective assessment is very difficult to achieve, even more if it deals with competencies. In this paper a new method for competencies assessment is proposed. It tries to be as objective as possible. More specifically, the paper deals with the ability to work on interdisciplinary teams, personal initiative, creative skills, personal autonomy, systematization and honesty competency. It also shows that the proposed method is robust against an intention to be learnt by students. The paper also describes some experiences with proposed evaluation method in one mechatronic course of the Industrial Engineering at ICAI (Comillas).